Keluwih (Artocarpus camansi) extract effects in zebrafish models of Parkinson’s disease - Marisca Evalina Gondokesumo; Krisyanti Budipramana; Putu Dea Angelita Putri; Ni Putu Diah Nopitasari; Martanty Aditya; Liza Yudistira Yusan (Jurnal Teknologi Laboratorium)
Parkinson’s disease is a condition that affects the central nervous system in the brain and is brought on by a lack of dopamine. Uncontrollable tremors, uncoordinated movement, and stiffness characterize Parkinson’s disease. Until now, the medication for Parkinson’s disease is limited to relieve the symptoms and maintain the quality of life; thus, the progression of the disease can be delayed. In order to search for alternative therapy from herbs, Kluwih (Artocarpus camansi) has been used traditionally to relieve convulsants. This research aims to observe 96% ethanol extract of A. camansi leaves in dopamine and locomotor activity in adult male and female zebrafish (Dario rerio). The A. camansi extract concentration was 2.5; 5; 7.5; and 10 mg/ml for 28 days. Zebrafish locomotion was observed for 5 minutes on days 0; 7; 14; 21; and 28. ELISA measured the observations of dopamine after 28 days. The 96% ethanol extract of A. camansi leaves at 5 mg/ml can increase dopamine levels after induced with rotenone, but the dopamine level decreased at 7,5 and 10 mg/ml. The maximal concentration to increase locomotor activity is also at 5 mg/ml, along with dopamine concentration. Our findings revealed that 5 mg/ml of 96% ethanol extract of A. camansi leaves was the optimal dosage to stimulate dopamine release and enhance locomotor activity.